2005
DOI: 10.1007/s00439-005-1326-8
|View full text |Cite
|
Sign up to set email alerts
|

FMR1 repeat sizes in the gray zone and high end of the normal range are associated with premature ovarian failure

Abstract: Premature ovarian failure (POF) is the occurrence of menopause before the age of 40 and affects 1% of the female population. Whereas the etiology of POF is largely unexplained, FMR1 premutation carriers are known to be at increased risk of POF compared with the general population. The FMR1 premutation alleles have 55-200 copies of a CGG repeat in the 5' untranslated region of the FMR1 gene. However, functional effects on gene expression may occur even for repeat sizes in what has been considered the "normal" r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
142
6
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 172 publications
(157 citation statements)
references
References 43 publications
(42 reference statements)
6
142
6
3
Order By: Relevance
“…14 By contrast, among women with POI but without cases of the fragile X syndrome among close family members, the prevalence of full mutations and premutations was much lower, with the latter varying from 2.2 26 and 2.5 27 to 4.9%. 4 Among infertile women with reduced ovarian reserve but without POI, the prevalence rates of the premutation tended to be even lower, varying between 1.3 28 and 5.6%. 29 In this study, in which the cohorts were selected based on (in) fertility issues entirely unrelated to the fragile X syndrome, the prevalence rates of expanded FMR1 CGG repeats among fertile women were comparable with known population-based incidence rates, whereas those of infertile women were comparable with the incidence rates found in another large scale survey among infertile women.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…14 By contrast, among women with POI but without cases of the fragile X syndrome among close family members, the prevalence of full mutations and premutations was much lower, with the latter varying from 2.2 26 and 2.5 27 to 4.9%. 4 Among infertile women with reduced ovarian reserve but without POI, the prevalence rates of the premutation tended to be even lower, varying between 1.3 28 and 5.6%. 29 In this study, in which the cohorts were selected based on (in) fertility issues entirely unrelated to the fragile X syndrome, the prevalence rates of expanded FMR1 CGG repeats among fertile women were comparable with known population-based incidence rates, whereas those of infertile women were comparable with the incidence rates found in another large scale survey among infertile women.…”
Section: Discussionmentioning
confidence: 95%
“…28 The number of women with expanded FMR1 CGG repeat numbers in this cohort among the women with overt POI was comparable to the incidence rates reported previously. 4,26 The review of all published controlled studies on the prevalence rates of expanded FMR1 CGG repeat numbers revealed that in the absence of a familial risk, the relative risk of carrying the premutation among infertile women with reduced ovarian reserve and/or POI was marginally increased 13,27 or similar 4,28,29 in all but one study. 30 The prevalence rates of CGG repeat lengths of the intermediate range were similar among infertile women with reduced ovarian reserve and/or POI in all reviewed studies.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations